Reading Egils saga Skallagrímssonar - Capildeo, S (2000)
﻿ This thesis is concerned with how a set of different texts, all titled with various English or Icelandic versions of Egils saga, exists, can be interrelated, and may be read. The first level of interpretation, before reading of the text even begins to occur, is a response to the book as a physical object whose ordering encourages and excludes certain interpretations. The first two chapters analyze the six English translations of Egils saga: W.C. Green (1893), E.R. Eddison (1930), Gwyn Jones (1960), Christine Fell and John Lucas (1975), Hermann Palsson and Paul Edwards (1976), Bernard Scudder (1997): together with the Icelandic editions used as their source texts, in terms of paratext, as developed by Gerard Genette. The third chapter consists of translation analyses. These use some of the methods of traditional translation criticism, together with more liberal methods of analysis associated with 'Translation Studies', as established by Susan Bassnett, among others. I conclude that the reader of translations who intends to move between 'target language' (language of translation) and 'source language' (language for translation), or who is in the process of getting the freedom to make transitions between these languages, is a special case, and that there is a literature which exists for them. By this I mean that, while it can be liberating to read literary translations as works 'in their own right', there are areas in some literary translations where it is best, or possible, to manipulate several languages and culture levels. There are also literary translations where the play between source language and target language, texts and paratexts, is necessary to their existence. Although I retain the 'source' and 'target' terminology of Translation Studies, I begin the chapter by questioning the direction of the vector: "target" texts are in some senses the 'source' texts for the 'source' texts subsequently encountered by readers between languages. The final chapter studies processes of transformation in Egils saga, following the Islenzk fornrit text. It shows how the saga itself is concerned with the meaning and powers of language and processes of transmission: it translates itself, not in a modern self-reflexive sense, but with its own, historically particular aesthetic.